From the press release to the utilitarian news - Vásquez Chaparro, Hellen (2019)
This article explains how the use of a well-written press release will allow the transmission of relevant information from the company to the news editors (on various information platforms), as well as its construction so that it becomes material valuable and utilitarian; and how it should be sent, to get the journalist's attention. It is important to remember that journalists can obtain the information by presenting themselves at the scene (an event, a press conference, etc.), or by a coordinated interview (with an entity or person) or through a well-structured note of press.